2020
DOI: 10.1371/journal.pone.0237186
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate prescriptions according to explicit and implicit criteria in patients with multimorbidity and polypharmacy. MULTIPAP: A cross-sectional study

Abstract: Background Multimorbidity is a global health challenge that is associated with polypharmacy, increasing the risk of potentially inappropriate prescribing (PIP). There are tools to improve prescription, such as implicit and explicit criteria. Objective To estimate the prevalence of PIP in a population aged 65 to 74 years with multimorbidity and polypharmacy, according to American Geriatrics Society Beers Criteria ® (2015, 2019), the Screening Tool of Older Person's Prescription-STOPP-criteria (2008, 2014), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 53 publications
(89 reference statements)
9
35
2
Order By: Relevance
“…Moreover, the results show that T2DM is more prevalent among the 65–70 years age group. The results of our study are similar to the recent study that applied 2019 Beers Criteria on patients aged 65–74 years attending primary care centers in Spain and which reported a PIM prevalence of 68.8% [ 22 ]. Furthermore, another recent study by Sharma et al reported that nearly 62% of older patients aged 65–70 years received at least one PIM during hospitalization [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the results show that T2DM is more prevalent among the 65–70 years age group. The results of our study are similar to the recent study that applied 2019 Beers Criteria on patients aged 65–74 years attending primary care centers in Spain and which reported a PIM prevalence of 68.8% [ 22 ]. Furthermore, another recent study by Sharma et al reported that nearly 62% of older patients aged 65–70 years received at least one PIM during hospitalization [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results show that the most prescribed PIMs were PPIs and long-acting sulfonylureas. The use of PPIs coincides with other studies (Fralick et al 2020;Lopez-Rodriguez et al 2020;Roux et al 2020;He et al 2021). Overuse of PPIs is a problem worldwide (Forgacs and Loganayagam 2008;Voukelatou et al 2019) as it is in Jordan (Alqudah et al 2016) due to their relative superior efficacy and high safety compared to H2 receptor blockers.…”
Section: Discussionsupporting
confidence: 77%
“…In other studies conducted worldwide for the use of PIMs according to 2019 AGS Beers Criteria, the prevalence ranged from 34.1 to 68.8%. These studies were conducted in Lebanon (34.1%) (Chahine 2020), in USA (34.4%) (Clark et al 2020), in China (35.0%) (Huang et al 2020), in Switzerland (53%) (Achterhof et al 2020), and in Spain (68.8%) (Lopez-Rodriguez et al 2020). The difference in prevalence is predicted and comparing other studies should be made with caution due to differences in population studied, time of the study, source of patient information, healthcare setting, and medication availability and accessibility in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotropic polypharmacy remains problematic [65], and polypharmacy can be associated with certain classes of medications, particularly central nervous system (CNS) drugs, anticholinergics, sedatives, and proton pump inhibitors [66][67][68]. Several epidemiological studies have demonstrated that potentially inappropriate prescribing increases with polypharmacy [69][70][71][72][73]. Similar trends have been observed in care home populations and people with dementia [74,75].…”
Section: Prescribing In the Face Of Multimorbiditymentioning
confidence: 90%